Rankine cycle efficiency gain using thermoelectric heat pumps. (15th February 2015) - Siviter, J.; Montecucco, A.; Knox, A.R.
Highlights: Rankine cycle electrical power plant fuel load reduced by over 1.5 Thermoelectric heat pumps are used to increase the efficiency of the Rankine cycle. We scavenge the enthalpy released in the condenser for preheating the return water. We measure with a new test rig the optimum COP for maximum efficiency increase. We show a cost-benefit analysis of applying the system to a thermal power plant. Abstract: The Rankine cycle remains the dominant method of thermal plant electricity generation in the world today. The cycle was described over 150 years ago and significant performance advances continue to be realised. On-going metallurgy research has enabled the operating pressure and temperature of the boiler and turbine to be increased, thereby improving the cycle efficiency. The ubiquitous use of the Rankine cycle on a massive scale in conjunction with fossil fuels as the energy source continues to motivate further efficiency improvements in the cycle. Previous work established a theoretical basis for the use of thermoelectric heat pumps (THPs) in the condensation process of the Rankine cycle to positively impact cycle efficiency. The work presented here experimentally validates this prior work and provides performance metrics for current commercially available THPs and quantifies how their use can increase the efficiency of the Rankine cycle as implemented in a large power plant. A commercial THP is characterised to obtain its Coefficient of Performance (COP) variation with input current and the amount of thermal energy transported. A larger-scale system comprising of a multistage thermoelectric heat pump is then considered, demonstrating that using commonly available THPs a fuel load reduction of over 1.5% is achievable for a typical 600 MW e generating set whilst simultaneously increasing the overall plant cycle efficiency from 44.9% to 45.05%. The paper concludes with a cost-benefit analysis of the system, showing that over a four year period the saving in fuel used can easily re-coup the capital cost incurred by the addition of the condenser heat pump.